Peningkatan Pemahaman Konsep dan Kemampuan Penalaran Matematika Setelah Menggunakan Perangkat Pembelajaran Matematika Berbasis Discovery Learning Pada Kelas X SMA - Utami, Nita Putri (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Understanding the concepts and math reasoning ability of learners in schools has not developed optimally. This is because, teachers have not facilitate learners to be active in learning. In other words, learning done in schools has not been meaningful learning. One of the causes of mathematics learning tools used by educators has not supported the achievement of optimal learning objectives. The purpose of this research is to produce as learning device based on discovery learning mathematics on equation material and linear inequality that is valid, practical, and effective. This research is a development research using the Plomp development model consisting of initial investigation phase, prototype development or prototype phase, and assessment phase. The effectiveness data is obtained from the cognitive competence test sheet of the learner, observation sheet of students' affective competence and observation sheet of psychomotor competence of the learner. The results showed that the learning tools of mathematics developed were valid, practical and effective. In this journal only discussed increased understanding of the concept and the ability of mathematical reasoning of learners after use of learning devices based on discovery learning mathematics.Keywords: Discovery Learning, Conceptual Understanding and Reasoning Math Abilities.